The ageing workforce in Ireland: Working conditions, health and extending working lives - Ivan Privalko; Helen Russell; Bertrand Maître (The Economic and Social Research Institute (ESRI), 2019)
New research carried out on behalf of the Health and Safety Authority examines who is most likely to stay in the workforce for longer and who is most likely to leave early.
Keywords: 330